Formulation of a modified release metformin.HCl matrix tablets : influence of some hydrophilic polymers on the release rate and in-vitro evaluation (2011)
ABSTRACT: Metformin hydrochloride is an antidiabetic agent which improves glucose tolerance in patients with type 2 diabetes and reduces basal plasma levels of glucose. In this study, a simplex centroid experimental design with 69 runs was used to select the best combination of some hydrophilic polymers that rendered a 24 h in-vitro release profile of metformin.HCl. The Korsmeyer-Peppas model was used to model the dissolution profiles since it presented the best fit to the experimental data. Further, a cubic model predicted the best formulation of metformin.HCl containing polyvinyl pyrrolidone, ethyl cellulose, hydroxypropyl methyl cellulose, carrageenan, sodium alginate, and gum arabic at 6.26, 68.7, 6.26, 6.26, 6.26 and 6.26 % levels, respectively. The validation runs confirmed the accuracy of the cubic model with six components for predicting the best set of components which rendered a once-a-day modified release hydrophilic matrix tablet in compliance with the USP specifications.